2010
DOI: 10.1007/bf03091779
|View full text |Cite
|
Sign up to set email alerts
|

Guideline adherence for antithrombotic therapy in acute coronary syndrome: an overview in Dutch hospitals

Abstract: Objective. To assess current Dutch antithrombotic treatment strategies for acute coronary syndrome (ACS) in light of the current European Society of Cardiology (ESC) guidelines. Methods. For every Dutch hospital with a coronary care unit (CCU) (n = 93) a single cardiologist was interviewed concerning heparin, thienopyridine and GP IIb/IIIa inhibitor (GPI) treatment. In each hospital, we randomly approached one cardiologist assuming equal policy among physicians employed at the same hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…however, in the actual guidelines of the ESMO concerning BTC,thistherapeuticregimewasapproved [3].Inoursurvey, abouthalfoftherespondentsstatedtousethecombinationof gemcitabineandcisplatinasfirst-linechemotherapy,butthe remainingrespondentsdeclaredtoapplyotherregimes.Considering that the participants were physicians interested in BTC,itseemsquestionablewhythenewtherapeuticstandard isnotadoptedtoagreaterextent.SimilarresultswerepublishedrecentlyforDutchhospitalswheretheguidelineadherenceforantithrombotictherapyinacutecoronarysyndrome was quite diverse [6]. Few data are available on how guidelinesaretransferredingeneralandifcompliancewithguidelinesledtobettertreatmentresults.AGermansurveyanalyzing the physicians' knowledge and their compliance with guidelinesforcardiovasculardiseasesrevealedthatphysicians who adequately knew the guidelines performed essentially notdifferentlyfromthosewhodidnot [7].Forbreastcancer, however, recent data suggest a better outcome for patients with guideline-conforming treatment.…”
supporting
confidence: 55%
“…however, in the actual guidelines of the ESMO concerning BTC,thistherapeuticregimewasapproved [3].Inoursurvey, abouthalfoftherespondentsstatedtousethecombinationof gemcitabineandcisplatinasfirst-linechemotherapy,butthe remainingrespondentsdeclaredtoapplyotherregimes.Considering that the participants were physicians interested in BTC,itseemsquestionablewhythenewtherapeuticstandard isnotadoptedtoagreaterextent.SimilarresultswerepublishedrecentlyforDutchhospitalswheretheguidelineadherenceforantithrombotictherapyinacutecoronarysyndrome was quite diverse [6]. Few data are available on how guidelinesaretransferredingeneralandifcompliancewithguidelinesledtobettertreatmentresults.AGermansurveyanalyzing the physicians' knowledge and their compliance with guidelinesforcardiovasculardiseasesrevealedthatphysicians who adequately knew the guidelines performed essentially notdifferentlyfromthosewhodidnot [7].Forbreastcancer, however, recent data suggest a better outcome for patients with guideline-conforming treatment.…”
supporting
confidence: 55%
“…The authors have concluded that an additional benefit may be achieved by the routine dose adjustment of LMWH for patients with renal insufficiency and aged over 75 years, since these patients are at high risk of bleeding complications secondary to antithrombotic treatment. 28 The contraindications; patients to whom heparins are prescribed for a long-term treatment; and patients with concomitant use of antithrombotic medicines, NSAIDs, and warfarin due to increased risk of ADRs. Low-molecular-weight heparins did not differ in terms of their safety parameters; therefore, the requirement for additional follow-up was not affected by the heparin brand or name prescribed for each patient.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…The European Society of Cardiology (ESC), American Heart Association (AHA) and American College of Cardiology (ACC) currently recommend the use of unfractionated heparin (UFH),enoxaparin or bivalirudin in STEMI patients undergoing PPCI [ 3 , 4 ]. Of these 3 agents, UFH is currently the most commonly used anticoagulant for this indication [ 5 , 6 ]. UFH was recently shown to be associated with lower rates of thrombotic events and similar bleeding events as compared to bivalirudin in a large scale all-comer randomized controlled trial reflecting contemporary practice (i.e.…”
Section: Introductionmentioning
confidence: 99%